2021
DOI: 10.18311/jbc/2021/26885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of <i>Metarhizium (Nomuraea) rileyi</i> (Farlow) Samson isolates against <i>Spodoptera litura</i> F. under <i>in vitro</i> conditions

Abstract: <p>Fifteen isolates of <em>Metarhizium</em> (<em>Nomuraea</em>)<em> rileyi</em> collected from field populations of <em>Spodoptera litura</em> (F.) and <em>Spodoptera frugiperda</em> J. E. Smith in different crops across different agroclimatic zones of Andhra Pradesh were evaluated for their pathogenicity against third instar larvae of <em>S. litura</em> at the Biocontrol Laboratory, Regional Agricultural Research Station, Tirupati, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In addition, the structure or composition of the integument at different developmental stages affects the infection and penetration of M. rileyi . On the other hand, the variation in the ability and number of surface-attached conidia of the strains against different developmental stages of insects may result in significant differences in the virulence of the two M. rileyi strains against different developmental stages of S. frugiperda [ 27 ].The data of the virulence of M. rileyi to different stages of S. frugiperda showed that the higher the concentration of spore suspension, the higher the mortality rate of the newly hatched larvae, the third and fifth instar larvae, and the adults, and pupation was significantly increased. This result is consistent with previous reports [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the structure or composition of the integument at different developmental stages affects the infection and penetration of M. rileyi . On the other hand, the variation in the ability and number of surface-attached conidia of the strains against different developmental stages of insects may result in significant differences in the virulence of the two M. rileyi strains against different developmental stages of S. frugiperda [ 27 ].The data of the virulence of M. rileyi to different stages of S. frugiperda showed that the higher the concentration of spore suspension, the higher the mortality rate of the newly hatched larvae, the third and fifth instar larvae, and the adults, and pupation was significantly increased. This result is consistent with previous reports [ 28 ].…”
Section: Discussionmentioning
confidence: 99%